2018
DOI: 10.1002/chem.201800451
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of Asymmetrical Multi‐Antennary N‐Glycans to Dissect Glycan‐Mediated Interactions between Human Sperm and Oocytes

Abstract: Complex N-glycans of glycoproteins of the zona pellucida (ZP) of human oocytes have been implicated in the binding of spermatozoa. The termini of these unusual bi-, tri-, and tetra-antennary N-glycans consist of the tetrasaccharide sialyl-Lewis (SLe ), which was previously identified as the minimal epitope for sperm binding. We describe here the chemoenzymatic synthesis of highly complex triantennary N-glycans derived from ZP carrying SLe moieties at the C-2 and C-2' arm and a sialyl-Lewis -Lewis (SLe -Le ) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In hemizona assay, sialyl-Lewis x tetrasaccharide as well as neoglycoproteins terminated by sialyl-Lewis x showed significant inhibition of human sperm-ZP binding ( Clark, 2013 ). By using chemoenzymatically synthesized highly complex triantennary N -glycans again confirmed that sialyl-Lewis x moiety is critical for human sperm-egg binding ( Chinoy et al, 2018 ). On the other hand, eggs obtained from transgenic mice expressing human ZP2, mouse ZP1, and mouse ZP3 that bind human sperm do not show expression of sialyl-Lewis x expression suggesting that it may not be critical for sperm-egg binding ( Avella et al, 2014 ).…”
Section: Role Of Zp Glycans In Human Oocyte-sperm Binding and Inductimentioning
confidence: 89%
“…In hemizona assay, sialyl-Lewis x tetrasaccharide as well as neoglycoproteins terminated by sialyl-Lewis x showed significant inhibition of human sperm-ZP binding ( Clark, 2013 ). By using chemoenzymatically synthesized highly complex triantennary N -glycans again confirmed that sialyl-Lewis x moiety is critical for human sperm-egg binding ( Chinoy et al, 2018 ). On the other hand, eggs obtained from transgenic mice expressing human ZP2, mouse ZP1, and mouse ZP3 that bind human sperm do not show expression of sialyl-Lewis x expression suggesting that it may not be critical for sperm-egg binding ( Avella et al, 2014 ).…”
Section: Role Of Zp Glycans In Human Oocyte-sperm Binding and Inductimentioning
confidence: 89%
“…One application of the above method was the assembly of some tri-antennary N-glycans of zona pellucida carrying sialyl Lewis X (SLe x ) moieties at the C-2 and C-2' arms and a sialyl Lewis X-Lewis X (SLe x -Le x ) residue at the C-6 antenna and another two analogs. The synthesized compounds were used to analyze the glycan-dependent interactions between human sperm and oocytes, indicating that the SLe x -Le x residue is essential for the inhibiting effect, while the other SLe x moieties showed much less effect (Chinoy et al, 2018).…”
Section: Different Types Of N-glycans Synthesized By Chemo-enzymatic Methodsmentioning
confidence: 99%
“…Boons and co‐workers also synthesized the complex N ‐glycans by installing different protecting groups on the core pentasaccharide 124 , including Lev, Fmoc, allyloxycarbonate (Alloc), and 2‐naphthylmethyl (Nap) groups (Scheme 26). [71] These protecting groups were orthogonally removed, which was followed by sequential glycosylation with donors 125 , 128 and 131 to afford the regioselective glycosylation product 132 . The yield of each coupling step is 91 %, 52 % and 75 %, respectively.…”
Section: Chemical Synthesis Of Glycansmentioning
confidence: 99%